Losartan reduces oxidative damage to renal DNA and conserves plasma antioxidant capacity in diabetic rats. (November 2015) - Lodovici, Maura; Bigagli, Elisabetta; Tarantini, Francesca; Di Serio, Claudia; Raimondi, Laura
Increased reactive oxygen species (ROS) levels produced by hyperglycemia and angiotensin-II (AT-II) are considered among the pathogenic factors in the malignant transformation of diabetic renal cells. We aimed to investigate the potential role of AT-II in the increased cancer risk seen in diabetes; measuring oxidative damage to renal DNA and protective antioxidant defenses, including adiponectin (Adp) and plasma antioxidant capacity by the Ferric Reducing Ability of Plasma (FRAP) method. In the kidney of streptozotocin (STZ)-induced (55 mg/kg) diabetic rats either treated or not treated for 3 weeks with losartan, an AT-II type 1 receptor antagonist (20 mg/kg/day); we measured 8-oxo-7, 8-dihydro-2′-deoxyguanosine (8-oxodGuo) levels, as an index of oxidative DNA damage, circulating Adp and FRAP. Diabetic rats showed significantly higher 8-oxodGuo levels in renal DNA (8.48 ± 0.98 × 10 −6 dG, mean ± SEM n = 11) than normoglycemic ones (1.18 ± 0.04 × 10 −6 dG, mean ± SEM, n=7) and lower plasma Adp and FRAP levels in comparison to normoglycemics. The treatment of diabetic rats with losartan significantly ( P  < 0.01) reduced 8-oxodGuo levels (5.4 ± 0.58 × 10 −6 dG, mean ± SEM n=9) in renal DNA and conserved FRAP values. Moreover, an inverse correlation was found between 8-oxodGuo in kidney DNA and circulating Adp levels in normoglycemic and diabetic rats. Losartan treatment preserves FRAP levels, reduces DNA oxidative injury and thus the carcinogenesis risk. Furthermore, our results indicate that Adp plasma levels are a further marker of oxidative injury to the kidney and confirm that it is an important part of the plasma antioxidant defense.